The utilization of aerial potato (Dioscorea bulbifera) (2000)
This study endeavored to experiment the versatility of an indigenous plant tuber Aerial Potato (Dioscorea bulbifera). Its being akin to potato implied that it can also be utilized the way potatoes are used as staples, vegetable, and snack food. It was further deduced that as tuber, it should be rich in carbohydrates, hence can be turned into flour for making desserts. Using tubers which had been stored for two weeks, aerial potato was boiled as staple, used in a meat recipe as vegetable for Menudo, prepared into French Fries and Potato Chips and turned into flour for the preparation of Polvoron. Taste Evaluation results showed that indeed it can be combined with camote which is another root crop and can even be used all by itself as staple, vegetable, snack foods, and dessert with mean scores ranging from 2.3 to 4.7 in a rating scale of 1 to 5 with 5 as the highest score.
Keywords: Potatoes